Challenges in Treatment Strategies for Management of Neonatal Sepsis (Journal of Dhaka Medical College, 2021)
Background: Neonatal sepsis is an important cause of morbidity and mortality in newborns. The symptoms and signs of neonatal sepsis are often non-specific and similar to other common neonatal diseases, investigation results are also non-specific and low sensitivity of blood culture also causes diagnostic dilemma and often empirical antibiotic treatment is given. This is why, there is challenges in making the diagnosis and treating neonatal sepsis.Objectives: To find the etiology, sensitivity and specificity of clinical features and investigations and optimal and effective treatment for neonatal sepsis.Materials and methods: The study was a prospective study done in the neonatal ward of a tertiary hospital in Bangladesh; total 100 neonates diagnosed as neonatal sepsis, were enrolled in this study. All study subjects were fully evaluated clinically, thoroughly investigated and properly treated as per protocol.Results: The sensitivity and specificity of clinical features and investigations were statistically significant (i.e. p